miR-148-3p inhibits gastric cancer cell malignant phenotypes and chemotherapy resistance by targeting Bcl2 - Hongyan Zhang (Taylor & Francis Group, 2021)
Gastric cancer(GC) is the fourth most common cancer in the world. This work was designed to explore the biological effects of miR-148-3p on GC. Quantitative reverse transcription-polymerase chain reaction (RT-qPCR) was utilized to analyze the mRNA expression of miR-148-3p in GC cell lines. The mimics and inhibitors of miR-148-3p, was carefully transfected into GC cells to up-regulate or down-regulate miR-148-3p expression. Observe the effect on miR-148-3p expression change to GC cell proliferation, colony formation, tumorigenesis, chemotherapy sensitivity, trans-well migration and invasion. Use online database tool to predict the miR-148-3p promising targets, and be verified via RT-qPCR, Western blot and luciferase report. We found that miR-148-3p expression level in GC cells was markedly down-regulated (P <0.05), as compared with human normal gastric mucosal cells GES-1. Otherwise, miR-148-3p overexpression could effectively inhibit the cell proliferation, cell cycle progress, colony formation, anti-apoptosis, anti-migration and anti-invasion in gastric cancer cells, whereas miR-148-3p inhibition exhibited the opposite phenomenon (P<0.05). Further research revealed that Bcl2 set as a direct downstream target of miR-148-3p. Our study firstly confirmed that, miR-148-3p might play a crucial role in tumorigenesis, as well as development of gastric cancer by targeting Bcl2, and could become a promising target for gastric cancer treatment.